Incident of sihir upon prophet Muhammad PBUH: analyses of narrations, mental capacity, and its implication on revelation - Mohamad, Mohd Yusof; Ramle, Muhamad Rozaimi (2021)
Introduction: The incident of sihir inflicted upon Prophet Muhammad PBUH is well-documented in traditions and historical narrations. Most scholars accept the incident indeed occurred and affected the mental capacity of the prophet in a limited manner. Anti-Islamic proponents use this as means to cast doubt on revelation. The current study sought to show the context of the mental disturbance and the implication upon revelation based on various narrations. Method: The incident of sihir was extracted from various classical hadeeth sources using Maktabah Shamela. Relevant scholarly opinions were selected and scrutinized for the incident. Results: The incident was authentic and reported in the major books of hadith, especially Sahih al-Bukhari and Muslim. Aisyah, Zaid bin Arqam and Ibnu Abbas were the companions who reported this incident. The context of the narration does not show satanic possession of the prophet either in anyway jeopardize revelation. The mental capacity minimally affected in which he only imagined himself together with his wife. The period of sihir is well documented, with no revelation was revealed during the incident. The prophet himself was very aware of the post-event and even did not take action on the person. Conclusion: Therefore, it can be deduced the incident did not doubt the integrity and the credibility of the prophet PBUH in transmitting revelation.